Changes in rowing technique over a routine one hour low intensity high volume training session - Mackenzie, H. A. M.; Bull, A. M. J.; McGregor, A. H. (Journal of Sports Science & Medicine, 2008)
ABSTRACT High volume low intensity training sessions such as one hour rowing ergometer sessions are frequently used to improve the fitness of elite rowers. Early work has suggested that technique may decline over this time period. This study sought to test the hypothesis that "elite rowers can maintain technique over a one hour rowing ergometer session". An electromagnetic device, in conjunction with a load cell, was used to assess rowing technique in terms of force generation and spinal kinematics in six male elite sweep oarsmen (two competed internationally and the remainder at a club senior level). All subjects performed one hour of rowing on a Concept II indoor rowing ergometer using a stroke rate of 18-20 strokes per minute and a heart rate ranging between 130-150 beats per minute, following a brief 5 minute warm- up. Recordings of rowing technique and force were made every 10 minutes. The elite group of rowers were able to sustain their rowing technique and force parameters over the hour session. Subtle changes in certain parameters were observed including a fall in force output of approximately 10N after the first seven minutes of rowing, and a change in leg compression of three degrees at the end of the one hour rowing piece which corresponded with a small increase in anterior rotation of the pelvis. However, it is unclear if such changes reflect a "warm-up" effect or if they are indicative of early signs of fatigue. These findings suggest that low intensity high volume ergometer rowing sessions do not have a detrimental effect on the technique of a group of experienced and highly trained rowers.